Keadilan Dalam Perspektif Hadis - Siddeh, Khoirul Anam (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2021)
This paper will discuss the hadith about justice related to the justice of a leader is leading. This initiative aims to make an inventory of the traditions about justice in leadership, to see the takhrij of the hadiths to see the quality of the hadiths, and to see the meaning of the hadith content with the justice of leaders and the relevance of justice in Islamic educational institutions. The research method in using the library research method with the maudu'i approach. The author searches for data by making an inventory of the hadiths in the nine books of hadith according to the hadith theme, then performs hadith takhrij and discusses the hadiths and relates them to the justice of leaders in educational institutions. The result is that 45 hadiths discuss justice, and one hadith that is most relevant to the theme is the hadith contained in Sunan Ad-Darimi number 2403. The hadith's takhrij is denied that the hadith is authentic. The concept of a leader in a broad sense is a person who has responsibility in any case, and everyone who has dependents is a leader. Responsible leadership before humans and before Allah SWT. Likewise with leadership in Islamic educational institutions. A fair leader must have scientific skills, be devout, have integrity, be honest, care, and not discriminate against the people he leads.